1H NMR plasma metabolomic profiling of ovarian quiescence in energy balanced postpartum dairy cows. Issue 1 (1st January 2018) - Zhang, Jiang; Wang, Gang; Zhao, Chang; Bai, Yunlong; Shu, Shi; Fan, Ziling; Xia, Cheng
Abstract: Background: As the milk production of dairy cows increases, the reproductive capacity gradually declines. Ovarian quiescence has become one of the concerns of the dairy industry. Objective: To explore the different plasma metabolite levels between estrus and anestrus in energy balanced (EB) dairy cows. Methods: Ten estrous and 10 anestrus EB Holstein cows in early lactation were selected for the study. 1 H nuclear magnetic resonance technology was used to detect plasma metabolites and screen different plasma metabolites between anestrous and estrous cows at 60–90 days postpartum using multivariate statistical analysis. Results: Within an elective waiting period of 60−90 days postpartum mean plasma concentration of total estrogens was significantly higher in estrus cows as compared to anestrus cows (71.2 ± 26.0 and 42.4 ± 16.7 pg/mL, respectively). Seven plasma metabolites (isoleucine, leucine, valine, alanine, arginine, choline and phosphatecholine) demonstrated significant decreases in estrous dairy cows relative to anestrous subjects. The main pathway was leucine, isoleucine and valine biosynthesis. Conclusion : Anestrus in dairy cows is accompanied by alterations in amino acid, glucose and lipid metabolism based on 1 H NMR analysis.